PROMISING REAGENTS FOR EXTRACTING STRATEGIC METALS FROM CHALLENGING MINERAL RAW MATERIALS - Elmuradov T. F.; Mamirov J. X. (Bright Mind Publishing, 2025)
The mining and processing industry is increasingly in need of new specialized reagents due to the declining quality of the ores being processed. The low gold content (below 0.5-1.0 g/t) and finely dispersed gold inclusions (0.1-10.0 microns) in ores, combined with the similar characteristics of separated minerals, significantly hinder flotation performance when traditional reagents are used. This often results in considerable losses of valuable metals in the enrichment tailings. Expanding the selection of domestic flotation reagents, informed by the latest advancements in fundamental research, is essential for mitigating the negative effects of the raw material's mineral composition and maximizing the recovery of strategic metals from challenging ores. Utilizing modern research techniques—such as scanning electron and laser microscopy, UV spectrophotometry, XRF, and chemical analysis—has allowed for the visualization of the adsorption layer of new collector reagents, specifically various dithiocarbamates, on gold-containing sulfides. The experimental determination of the quantity of adsorbed reagents on mineral surfaces revealed unique fixation characteristics that led to optimized consumption ratios in the flotation process. These scientifically tailored reagent protocols resulted in a 5-6% increase in gold concentration in the concentrate and a reduction in gold losses in the tailings during the flotation enrichment of refractory ore from the Malinovskoe deposit.
Keywords: Gold-bearing minerals; challenging ores; flotation reagents; morpholindithiocarbamate; cyanethyl-diethyldithiocarbamate; plant modifier; extraction.